(untitled) (Eurasian Journal of History, Geography and Economics, 2024)
The article describes the role of preschool educational institutions in the everyday life of rural residents of the Surkhandarya region in the 1960s-1980s, the construction and operation of preschool educational institutions, and their existing problems. Also, seasonal kindergartens in the villages, work done on training teachers and existing problems in this field were also analyzed.